Implementación de recursos didácticos interactivos de literatura infantil, para el laboratorio de práctica docente en la Universidad Técnica de Cotopaxi extensión La Maná, año 2014 - Zarabia Calero, Geovanna Estefania (2015)
The lack of teaching materials in the XXI century causes problems in the classroom as; little interest in class by students, is why the proposal for an interactive CD that complements the kind of children's literature with appropriate content to call the attention of the student when the class is raised are new resources, flashy and also education for pedagogical foundations supported by ICTs. The methodology is documentary - bibliographic and descriptive as education issues and the importance of children's literature, the benefits you get when you teach children reading benefiting students of basic education, focused and at the same time their skills are strengthened. By having an interactive CD it arises raise student interest in the subject under each level of education.